2013
DOI: 10.4269/ajtmh.12-0728
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Diagnosis and Genotype Identification of Scrub Typhus from Pinggu District, Beijing, 2008 and 2010

Abstract: Abstract. This study was conducted to determine the diagnosis and genotype of Orientia tsutsugamushi in Pinggu district, Beijing. Indirect immunofluorescence assay (IFA) was performed to detect O. tsutsugamushi-specific immunoglobulin M (IgM) and immunoglobulin G (IgG) antibodies. Nested polymerase chain reaction (PCR) and DNA sequencing analysis targeting the O. tsutsugamushi-specific groEL gene and 56 kDa protein gene were performed on whole-blood samples from scrub typhus patients. We confirmed that 47 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 18 publications
(15 reference statements)
0
8
0
Order By: Relevance
“…An eschar is not observed in every confirmed patient, and cutaneous lesions from other diseases, e.g., spider bites, leishmaniasis, spotted fever rickettsiosis and anthrax, may make the presence of an eschar less than a definitive diagnostic sign. Scrub typhus can be misdiagnosed as many acute febrile illnesses, including malaria, dengue, leptospirosis, other rickettsioses, meningococcal disease, typhoid fever, infectious mononucleosis and HIV [ 6 , 198 , 199 ].…”
Section: Discussionmentioning
confidence: 99%
“…An eschar is not observed in every confirmed patient, and cutaneous lesions from other diseases, e.g., spider bites, leishmaniasis, spotted fever rickettsiosis and anthrax, may make the presence of an eschar less than a definitive diagnostic sign. Scrub typhus can be misdiagnosed as many acute febrile illnesses, including malaria, dengue, leptospirosis, other rickettsioses, meningococcal disease, typhoid fever, infectious mononucleosis and HIV [ 6 , 198 , 199 ].…”
Section: Discussionmentioning
confidence: 99%
“… 16 However, recent studies have shown that DM prevalence among TB cases is variable and it ranges from 29.3% in Southern Mexico to 11.4% in Georgia USA 17 , 18 Studies conducted in Africa reported low prevalence of DM among TB patients; 8.5% in Uganda, 8.3% in Ethiopia, 2.8% in Guinea-Bissau and 1.9% in Benin. 13 , 19 21 Some studies have shown high prevalence of DM among TB patients; 29.5% in Taiwan, and 25.3% in India 22 , 23 …”
Section: Introductionmentioning
confidence: 99%
“…Until the 1980s, scrub typhus cases primarily occurred in the regions south of Yangtze River with established natural foci including Zhejiang in the east and Yunnan in the west part of China [ 13 , 14 ]. However, with rapid societal development, changing environment, climate change, population movement, better recognition by health care professionals and ever-improving detection techniques, both sporadic cases and disease outbreaks began to be identified in the northern provinces of Shandong, Jiangsu, Tianjin and Beijing, as well as the emergence of new natural foci in the past three decades [ 13 , 15 17 ]. Currently, the disease is widespread in most of the provinces in mainland China, where the incidence has increased rapidly in recent years.…”
Section: Introductionmentioning
confidence: 99%